Annual Plan 2003-2004 Draft Proposals Government of Meghalaya - Planning Commission (Planning Commission, 2003)
Area & Location: Meghalaya was first created as an Autonomous State within the State of Assam on the 2nd April, 1970 with the two erstwhile Districts of Assam, viz: the United Khasi & Jaintia Hills District and the Garo Hills District. The Autonomous State was upgraded into a full fledged State with effect from the 21st January, 1972. The State has a geographical area of 22,429 Sq. Kms approximately and has now 7 Districts viz : (I) the East Khasi Hills District (ii) the West Khasi Hills District (iii) the Jaintia Hills District (iv) the Ri-Bhoi District (v) the West Garo Hills District (vi) the East Garo Hills District and (vii) the South Garo Hills District. At the beginning, the State has 24 C&RD Blocks but the number has increased to 39 by the end of 2000-2001. It is one of the smallest States in India and is strategically located in the North-East between 25° 5” and 26° 10” North Latitudes and between 98° 47” and 97° 47” East Longitudes. It is a strip of land spread along the northern boundary of Bangladesh and it is bounded by that country on the South as well as on the West.
Planning Department Government of Meghalaya